Improving Public Sector Performance : Through Innovation and Inter-Agency Coordination - World Bank Group (World Bank, Washington, DC, 2018)
This report is an inaugural issue in a new series that aims to offer a fresh look at how developing countries are overcoming persistent problems in public sector management. Significant improvements in public sector performance are being evidenced across the developing world today, as government officials and political leaders find new and innovative ways to tackle long-standing challenges. Part I of this report demonstrates that public sector performance is being pursued diligently and successfully across a variety of country contexts, including in low-income environments. Through surveying its governance specialists from around the globe, the World Bank has assembled a collection of 15 cases that showcase how lessons from global experience are being adapted and applied in practice. The report also explores common success drivers that appear in each of the cases. Part II focuses on a special, cross-cutting topic that is critical to public sector performance -- policy and inter-agency coordination. As the responsibilities of government have grown in volume and complexity, policy and program coordination has become ever more challenging, and the stakes have never been higher. Enhancing coordination will depend not only on the adopted formal institutional mechanisms, but also on their interplay with the broader institutional environment and with other processes that influence coordination.